Three‐Dimensional Transformation of Membrane‐Type Electronics Using Transient Microfluidic Channels for the Sequential Selective Plasticization of Supportive Plastic Substrates. Issue 4 (13th November 2022) - Cha, Jihun; Kim, Gi‐Gwan; Kim, Seung Hyun; Park, Dukkyu; Yoo, Jung Il; Jang, Hun Soo; Yoon, Jongwon; Ko, Heung Cho
Abstract: This study demonstrates a technique for the development of 3D electronics based on planar membrane‐type devices and a supportive plastic (e.g., acrylonitrile butadiene styrene [ABS] used in this study) substrate containing internal microfluidic channels ( µ ‐FCs) that allow selective plasticization and transformation after the insertion of a liquid plasticizer (e.g., N, N ‐dimethylformamide). The internal µ ‐FC has a strong advantage of transiency and does not require an additional removal process because the channels are self‐closed by the swelling and dissolution of the plasticized regions. Furthermore, the 3D printing process to create internal µ ‐FCs provides a considerable amount of freedom in channel design for sequential plasticization and transformation into complex structures. Using this method, extreme scenarios that involve complete bending of the metal electrodes and indium gallium zinc oxide thin‐film transistors laminated to the ABS substrates without electrical failure are possible, regardless of the bending direction and the vertical position of the electrode of the plastic substrate. Finally, a truncated octahedral light‐emitting diode display is successfully developed by multiple cycles of sequential plasticization and transformation processes to demonstrate the feasibility of this method. Abstract : A simple but powerful method for transforming membrane‐type electronic devices into desirable 3D shapes is demonstrated by using a mechanically supportive plastic substrate with spatially designed internal microfluidic channels to guide and contain a controlled amount of liquid plasticizer for selective plasticization and transformation.